94 Under- versus overdiagnosis: exploring the benefits and harms of a PCOS label and its impact on women's psychosocial wellbeing, lifestyle and behaviour. (20th August 2018) - Copp, Tessa; Hersch, Jolyn; McCaffery, Kirsten; Doust, Jenny; Dokras, Anuja; Mol, Ben; Jansen, Jesse
Abstract : Objectives: Diagnostic criteria for polycystic ovary syndrome (PCOS) were expanded in 2003, resulting in the inclusion of women with milder forms and a substantial increase in the total number of women diagnosed. This has raised concerns about overdiagnosis and unnecessary disease labelling. PCOS is associated with adverse reproductive, metabolic and cardiovascular outcomes, however not all women fitting the expanded criteria may be at risk of these. Women with PCOS also have higher rates of psychological distress than their peers. However, it is unclear whether this is due to the condition, its symptoms, or the psychological impact of being labelled with PCOS. We aimed to explore the benefits and harms of a PCOS label from the perspective of women diagnosed with PCOS who vary across the spectrum of disease severity, and investigate how the diagnosis affected their psychosocial wellbeing, lifestyle choices and behaviour. Method: Women diagnosed with PCOS aged 18–45 in Australia were recruited via Facebook. We conducted 25 semi-structured face-to-face and telephone interviews. Topics included experience with diagnosis and management, doctor-patient communication, information provision and diagnostic satisfaction, perceived benefits and harms of diagnosis, and impact of the diagnosis on psychological wellbeing, life decisions, behaviour and social environment. Interviews were audio-recorded, transcribed and analysed thematically. Results: Women expressed a range of experiences regarding the diagnosis and management of their condition. Perceived benefits included validation and explanation of bothersome symptoms, increased understanding about their body and why it behaves in certain ways, and better access to treatment. Perceived harms included increased worry and anxiety about the future, and misperceptions and confusion about fertility, which resulted in unplanned pregnancies among some women. Adverse impacts on self-esteem and relationships were also reported, as well as significant out of pocket costs for specialist appointments, screening tests and medication. Conclusions: Diagnostic criteria for PCOS have expanded without clear evidence of benefit. It is vital the benefits and harms of a diagnosis for women across the spectrum of symptom severity are investigated. Participants interviewed in this study described various positive and negative impacts of a diagnosis on their lives, which were influenced by factors such as symptom severity, communication at diagnosis and their relationships with their clinicians. The implications of these findings for future research and clinical practice will be discussed.